2020
DOI: 10.3390/ijms21186515
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Angiogenesis, Lymphangiogenesis, and Epithelial–Mesenchymal Transition (Plasticity) in CIN and Early Invasive Carcinoma of the Cervix: Exploring Putative Molecular Mechanisms Involved in Early Tumor Invasion

Abstract: The establishment of a proangiogenic phenotype and epithelial-to-mesenchymal transition (EMT) are considered as critical events that promote the induction of invasive growth in epithelial tumors, and stimulation of lymphangiogenesis is believed to confer the capacity for early dissemination to cancer cells. Recent research has revealed substantial interdependence between these processes at the molecular level as they rely on common signaling networks. Of great interest are the molecular mechanisms of (lymph-)a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 127 publications
(175 reference statements)
0
8
0
Order By: Relevance
“…Genotyping of HUVEC cells collected after 48 h of incubations on PISEB, PLGA and PLGA/PISEB showed a potentially pro-angiogenic expression profile. Genes of neo-angiogenesis were observed to be in the cross-talk and correlations, and a feedback loop for upregulated MMPs, together with downregulated TIMP inhibitors, resulted in tissues with invasive and migratory cell phenotypes [ 41 , 42 ]. Under those conditions, cells cultured on the surface of PLGA/PISEB changed morphology into that typical for tube-formation specimens during neo-angiogenesis process [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping of HUVEC cells collected after 48 h of incubations on PISEB, PLGA and PLGA/PISEB showed a potentially pro-angiogenic expression profile. Genes of neo-angiogenesis were observed to be in the cross-talk and correlations, and a feedback loop for upregulated MMPs, together with downregulated TIMP inhibitors, resulted in tissues with invasive and migratory cell phenotypes [ 41 , 42 ]. Under those conditions, cells cultured on the surface of PLGA/PISEB changed morphology into that typical for tube-formation specimens during neo-angiogenesis process [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…After cells were trypsinized and collected, total RNA was isolated using the phenol-chloroform method of extraction, by the Total RNA Isolation kit (A@A Biotechnology, Gdańsk, Poland). The efficiency of RNA isolation was assessed spectrophotometrically, and amplification of genes was performed using commercially-available kits (Real-Time 2xPCR Master Mix SYBR A; A@A Biotechnology) and set of primers for IL8, VEGF, MMP2, MMP9, TIMP1 and TIMP2 (Genomed, Warsaw, Poland) from references [ 41 , 42 , 52 ]. The quantitative PCR reaction, preceded by reverse transcription (NG dART RT kit, EURx, Gdańsk, Poland), was performed using a CFX96 Touch™ Real-Time PCR Detection System thermocycler (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This result is consistent with a study that showed increased angiogenesis during fracture healing in a MATN1 deficient mouse, and purified MATN1 proteins enabled inhibition of angiogenesis both in vitro and in vivo 28 . Of note, VSTM4, FBLN5, MPZL3 and SCPEP1, have been reported to promote sprouting angiogenesis by endothelial cells 29,30,31,32 , while their role in retinal angiogenesis remains unstudied.…”
Section: Amdmentioning
confidence: 99%
“…Therefore, inhibiting angiogenesis has become one of the effective strategies in cancer therapy 15 . Numerous signaling molecules, such as VEGFA and TGF‐β, have been proven to modulate angiogenesis during cancer progression over the past decades 16,17 . Many studies reported that TUG1 is involved in angiogenesis during the progression of various diseases 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Numerous signaling molecules, such as VEGFA and TGF‐β, have been proven to modulate angiogenesis during cancer progression over the past decades. 16 , 17 Many studies reported that TUG1 is involved in angiogenesis during the progression of various diseases. 18 , 19 One miRNA in particular, miR‐29c‐3p, could be directly targeted by TUG1 to stimulate angiogenesis in endothelial progenitor cells and diabetic mouse ischemic limb.…”
Section: Introductionmentioning
confidence: 99%